If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 2x + -1(4x + 6) Reorder the terms: 5 + -1x = 2x + -1(6 + 4x) 5 + -1x = 2x + (6 * -1 + 4x * -1) 5 + -1x = 2x + (-6 + -4x) Reorder the terms: 5 + -1x = -6 + 2x + -4x Combine like terms: 2x + -4x = -2x 5 + -1x = -6 + -2x Solving 5 + -1x = -6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + -1x + 2x = -6 + -2x + 2x Combine like terms: -1x + 2x = 1x 5 + 1x = -6 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 1x = -6 + 0 5 + 1x = -6 Add '-5' to each side of the equation. 5 + -5 + 1x = -6 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = -6 + -5 1x = -6 + -5 Combine like terms: -6 + -5 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| -2+3y=4 | | 2x+2x+x+x=312 | | 5(x-2)-4=14 | | 4.3(x+3.7)-2.97=4.34 | | 2(b-4)=3(b-5) | | 3x=28-x | | 4+3y=4 | | 3/x=x-10/8 | | 11b+12=b+138 | | 10x-1=24 | | (1xy+8)(1xy-8)= | | (12*x-5*x*x-1)/(3*x-3)=0 | | -3(f+4)-2=2(f+8) | | -3x=16-5x | | -.75x^2=(81/4)=0 | | ?x-5-x=-5 | | x+(x+2)+(x+5)=63 | | ln(x-1)=3/4 | | 4(3d-5)-8d=7d+14 | | x+(x+5)+(x+2)=63 | | A*B+(1-A)*(C*D-(1-C)*E)=F | | 6x^2-17x-1=2 | | (6x-20)/3x-9 | | 15m=3(m-8) | | -.25x^3+20.25x=0 | | 3x^2-20x-15=-8 | | x=ln(x+1) | | 12/f=8/12 | | 12*x-5*x*x-1=0 | | -5v-4=v+158 | | 2(x+3)=4(3x-1) | | 11b^2-39b-20=0 |